Improving Healthcare through Data - GAO, Sarah Y. (Institutional Knowledge at Singapore Management University, 2023)
At a recent Singapore Management University’s (SMU) Healthcare Analytics and Operations Workshop, researchers, practitioners and policymakers shared their views on the Healthier SG movement and how investing in regular screening, counselling and vaccination can support preventative care.